Pentingnya Peran Guru Dalam Pembentukan Karakter Siswa Di Era Digital - Wila Mardiana; Opi Andriani; Nurul Salwa; Gipia Rohman (Pendekar : Jurnal Pendidikan Berkarakter, 2024)
This article aims to provide information in terms of how to remember the importance of improving character education in the 4.0 era where the human side is slightly threatened, there needs to be coordination between various parties including schools, families and the environment. Where at that time there was a change in the civilization of society which was marked by changes in the joints of life, culture, society, including education. As a source of knowledge, teachers also need to understand the technology that is developing at this time in order to guide or direct their students so as not to fall into today's modern technology. This research method uses literature and descriptive methods, researchers describe a phenomenon based on the experiences of research participants and the results of observations that have been made.